WORD OF MOUTH SEBAGAI STRATEGI KOMUNIKASI PEMASARAN SANGGAR WAYANG PURWANTO - Nur Wibowo, Pratama; Suryo, Herning; Widiyowati, Estu (Solidaritas, 2024)
ABSTRACT Wayang is a popular traditional art from Indonesia, especially in Java. On November 7, 2003, UNESCO recognized wayang kulit as a world cultural heritage, emphasizing the importance of preserving this art. In the era of globalization, fierce competition requires MSMEs, including art businesses, to implement effective marketing strategies in order to survive. One strategy that has proven effective is Word of Mouth or word-of-mouth promotion. Sanggar Wayang Purwanto, a traditional business in Central Java that was established in 1976, utilizes this strategy in marketing. Therefore, this study was conducted to describe the application of the Word of Mouth strategy in the Purwando Puppet Studio. The research method used was qualitative with the main respondents Mr. Purwanto, the owner of the studio, and his consumers. The results of the study show that Sanggar Wayang Purwanto uses two types of Word of Mouth: Amplified Word of Mouth triggered by the company, and Organic Word of Mouth which arises naturally from consumers. There are five key elements in the application of Word of Mouth in this studio: (1) Talkers—speakers from customers and close networks, (2) Topic—product quality, competitive prices, and friendly service, (3) Tools—direct communication and traditional information dissemination, (4) Talking Parts—engaging consumers through active responses, and (5) Tracking—monitoring customer satisfaction and responses without special supervision. But by maintaining quality and service. Keywords: marketing communication, word of mouth, puppet studio